Romansa Jalan Tunjungan dalam Konsep Urbanism Heritage - Sidik, Noer; Basundoro, Purnawan; Asmorowati, Sulikah; Nurhidayati, Sri Endah (Universitas 17 Agustus 1945 Surabaya, 2024)
The dynamics of modernisation and globalisation threaten the preservation of local traditions and cultural identity of local communities which include challenges to maintain traditional cultural values and practices amidst social, economic, and cultural changes caused by modernisation and global influences. The results show that the uniqueness of local culture, celebrations, and traditional festivals in Jalan Tunjungan which are maintained through the active role of local residents become an important pillar in maintaining tradition and cultural heritage in Tunjungan area, while strengthening its identity as an urban cultural heritage site in the midst of modernisationiterature study and interview which then analysed by contextual interpretation and data triangulation. The results show that the uniqueness of local culture, celebrations, and traditional festivals in Jalan Tunjungan which are maintained through the active role of local residents become an important pillar in maintaining tradition and cultural heritage in Tunjungan area, while strengthening its identity as an urban cultural heritage site in the midst of modernisation.